2020
DOI: 10.1177/1055665620904514
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Cervical Vascular Imaging in Patients With Velocardiofacial Syndrome and Velopharyngeal Dysfunction in the United Kingdom

Abstract: Objective: In patients with velocardiofacial syndrome (VCFS), medial displacement of the internal carotid arteries (ICAs) may increase the risk of vascular injury during the surgical correction of velopharyngeal dysfunction (VPD). Some surgeons advocate the use of vascular imaging studies prior to surgery. Nevertheless, the role of preoperative imaging is still controversial. This study aimed to review the current practice of the UK cleft units and also examine our own practice at the Evelina London Children’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…First, the presence of all ICA anomalies were collected, which encompassed medialization along with other ICA aberrancies, such as hypoplasia, tortuosity, kinking, and anterior deviation. 3,23,24,28,29,32 Vessels with a bifurcation at a more cranial or caudal level than expected or asymmetric vessels were not considered an anomaly. 3 Then, ICAs with medialization were specifically extracted, defined as deviating from a vertical course parallel with cervical vertebrae and instead aiming toward the pharyngeal midline 25% from normal course or more.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the presence of all ICA anomalies were collected, which encompassed medialization along with other ICA aberrancies, such as hypoplasia, tortuosity, kinking, and anterior deviation. 3,23,24,28,29,32 Vessels with a bifurcation at a more cranial or caudal level than expected or asymmetric vessels were not considered an anomaly. 3 Then, ICAs with medialization were specifically extracted, defined as deviating from a vertical course parallel with cervical vertebrae and instead aiming toward the pharyngeal midline 25% from normal course or more.…”
Section: Data Extractionmentioning
confidence: 99%
“…3,9,[18][19][20][21] In the usual position, the ICA is 1 to 1.5 cm away from the pharyngeal operative field; however, medialization can reduce this distance to millimeters. 22 The concern of ICA medialization in 22qDS velopharyngeal procedures was first described in 1987 by Mackenzie-Stepner et al 9,22,23 During routine preoperative nasopharyngoscopy to assess VPD, three children were noted to have posterior pharyngeal wall pulsations. The authors hypothesized that ICA displacement was causing the pulsations, which was then confirmed by imaging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations